Toxic Cardiac Manifestation in a Young Male with Organophosphate Poisoning with Breakthrough Seizures - Zahid, Osama; Iqbal, Madiha; Khan, Nadeemullah (British Journal of Healthcare and Medical Research, 2022)
Organ phosphorus compounds are used as pesticides and represent a common cause of poisoning in developing countries including Pakistan due to their widespread availability. Toxicity due to these agents can affect many organs including the heart. Here, we report a case of acute organophosphorus poisoning in a patient, followed by acute myocardial infarction; documented by clinical features, electrocardiographic changes, and elevated cardiac enzymes. This case report will help a physician to look for acute myocardial injury in a patient with OP poisoning to reduce fatal complications and improve mortality, as such presentation with OP poisoning is rarely seen especially in a pediatric population.